Socioenvironmental Conflict and Industrial Pollution: The Case of Rio Gramame-Mumbaia Basin – Pb - Nunes, Edilon Mendes (2013)
This is a case study of Political Ecology. It is an analysis of the Social Environmental Conflict of industrial pollution in the Basin of Rio Gramame, in the community of Mumbaba de Baixo. Although this conflict has begun in the decade of 1960, it has been recognized only recently. As we have sought to understand the complexities of this study, we draw a methodological road of analysis of the conflict based on each part of its components. In this way, we have identified all those involved, their actions, articulations, powers, and their influence on the conflict. We have used a social-anthropological approach by means of participant observation, with the "snowball" technique, as well as semi-structured interviews, mental models, analysis of perceptions and photographic records. We have found that actors are not articulated and the majority of them do not follow their script as defined by legislation, which impairs the perspectives of resolution and, as a result, the situation has been perpetuated. This study is relevant for bringing to surface all the voices that go unheard, and for this reason, it is a provocative work